COMPETENCIES AND EFFECTIVENESS OF POLISH BODIES ESTABLISHED TO COMBAT CORRUPTION: ANALYSIS OF THE ACTIVITIES OF THE CENTRAL ANTICORRUPTION BUREAUAND THE SUPREME AUDIT OFFICE - Chmiel, Tomasz (Management and Administration Journal, 2025)
The aim of the article is to present the concept, activities, and specificity of the Central Anticorruption Bureau (CBA) and the Supreme Audit Office (NIK) in the fight against corruption in Poland. The author discusses the problem of corruption in Poland, focusing on two main objectives of combating: the Central Anticorruption Bureau (CBA) and the Supreme Audit Office (NIK). The author draws attention to risks of corruption, such as public administration, health care and electoral procedures. The conclusions indicate that despite legal regulations and actions taken by the CBA and NIK, corruption in Poland is still a problem due to the lack of systematic actions and the high social risk for this type of activities.